1963
DOI: 10.1111/j.1365-2044.1963.tb13573.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐administered nitrous–oxide/oxygen analgesia in obstetrics

Abstract: In 1934 Minnitt 1 introduced an apparatus for the self-administration of nitrous-oxide/air analgesia in labour under the general supervision of the midwife. In 1949 Seward showed that the two main disadvantages of 'gas and air' were firstly, that the 50 % nitrous-oxide given by the apparatus was frequently too weak to provide adequate analgesia and secondly, that after breathing the mixture for a short time, the mother and the baby were likely to become hypoxic, a point recently confirmed by Cole and Nainby-Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…It has been observed by Kerr [7] and Heneghan et al [8] anaesthesia. Low levels of inspired oxygen are not new as 80% nitrous oxide in oxygen was used to relieve labour pain [9], for the treatment of angina [lo] and in dental anaesthesia [ll]. It can be concluded that the maintenance of the pre-operative Spo, value by using the minimum Ao, in nitrous oxide is not deleterious to patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed by Kerr [7] and Heneghan et al [8] anaesthesia. Low levels of inspired oxygen are not new as 80% nitrous oxide in oxygen was used to relieve labour pain [9], for the treatment of angina [lo] and in dental anaesthesia [ll]. It can be concluded that the maintenance of the pre-operative Spo, value by using the minimum Ao, in nitrous oxide is not deleterious to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cylinders containing a 50: 50 mixture of nitrous oxide and oxygen (Gale, Tunstall and Wilton-Davies, 1964) are now available, and their use by midwives has ibeen approved by the C.M.B. The latter body has also given its approval to the Lucy Baldwin gas and oxygen 'machine i (McAneny and Doughty, 1963), a modification of an older apparatus (the Walton Five). The Lucy Baldwin may be set to deliver oxygen in concentration ranging from 30%/, in nitrous oxide, up to 100%.…”
Section: Drugsmentioning
confidence: 99%
“…The proportions of mothers who were reported to have fallen asleep during contractions were 16.6% and 21.7% with the two mixtures of nitrous oxide and oxygen. Moreover, McAneny & Doughty (1963) reported an increase in the proportion rendered unconscious during inhalation of nitrous oxide from 1% with 50% N 2 O to 5% with 80% N 2 O. The subjective median VAS (0-100 mm) score for sedation during intermittent 50% nitrous oxide analgesia was 51 mm (range 13-100) in a cross-over study by .…”
Section: Sedationmentioning
confidence: 99%
“…The Committee report did not include any information as to which proportion of the parturients received additional tranquilizers or narcotics, but noted that this was not influenced by the concentration of nitrous oxide. McAneny et al (1963) reported 22%-42% of the parturients receiving more than one injection of analgesics. Hence, at least part of the reported pain relief could have been due to the effect of the adjuvant medication.…”
Section: Analgesia With Remifentanil Epidural Block and Nitrous Oxidementioning
confidence: 99%
See 1 more Smart Citation